Applications of the digital technologies in textile and fashion manufacturing industry - Rahman, Md. Mahbubur (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Recently, there have been increased demand and applications of digital technologies such as 3D printing, digital printing, radio frequency identification (RFID) and computer vision in textile manufacturing in order to improve the supply chain system and increase customer’s satisfaction. Moreover, these technologies help to ensure sustainability and enable manufacturers as well as retailers to respond promptly to market demand by reducing product lead-time. However, there are limited research on in-depth review on the applications of these technologies in textile manufacturing and fashion retailing. This research rigorously review the recent articles related on the applications of 3D printing, digital printing, radio frequency identification (RFID) and artificial intelligence in textile manufacturing. The review reveals that implementation these technologies reduces production cost and increases profitability. The authors also proposed models for the above-mentioned technologies that are applicable in textile and fashion industries.